Genetic polymorphisms of GSTP1 and XRCC1: prediction of clinical outcome of platinum-based chemotherapy in advanced non-small cell lung cancer (NSCLC) patients (Swiss Medical Weekly, 2011)
PRINCIPLES: Platinum agents cause DNA cross-linking and oxidative damage. Genetic polymorphisms of GSTP1 and XRCC1 involved in glutathione metabolic and DNA repair pathways may explain inter individual differences in chemosensitivity and clinical outcome in NSCLC patients treated with platinum-based regimens. METHODS: We used DNA sequencing methods to evaluate genetic polymorphisms of the GSTP1A313G and XRCC1G28152A in 111 patients with stage IV NSCLC treated with platinum-based chemotherapy. Clinical response was evaluated according to RECIST criteria after 2–3 cycles of chemotherapy and time to progression (TTP) was calculated from the time of initial treatment to disease progression. RESULTS: GSTP1A313G and XRCC1G28152A polymorphisms, both alone and in combination, were significantly associated with response to treatment and clinical outcome (p